The sickle-cell trait: A study of its distribution and effects in some Bantu tribes of South Central Africa - Peter Brain (Department of Medicine, 2024)
rhe scope of this work needs some explanation. I first became interested in the sickle-cell anomaly in 1951, while employed as a medical officer to an asbestos r::iining group in Southern .Rhodesia. Here I had :for investigation a population of several thousand adult male Bantu, very mixed as to tribe, drawn from a wide area of south Central Africa. The scope of this invest1gs,tion has been determined by the nature of the nmterial; vvbich is in some respects unusual. This will be fully described later, but the important point is that in this population sickle-cell anaemia, if it occurs at all, is very rare. The sickle-cell trait, on the other hand, is frequently seen, and in a fit adult population of this kind it appears to exist virtually unadulterated by cases of sickle-cell anaemia either active or latent. This makes the population a peculiarly advantageous one for a study of the trait in its pure form, and it is the trait, and not the anaemia, that is dealt with in this thesis. The anaemia is treated only incidentally, and I should ffiake it clear at the beginning that I can express no IL authoritative views on it.